Participation and Coordination between Companies and the Cirebon City Government in Poverty Alleviation through Corporate Social Responsibility Programs - Moh. Taufik Hidayat; Moh. Sutarjo (International Journal of Science and Society, 2021)
One of the crucial problems faced in the city of Cirebon is the poverty rate which is quite high and continues to increase from year to year. The Corporate Social Responsibility (CSR) program or Corporate Social and Environmental Responsibility (TJSL) according to Cirebon Mayor Regulation Number 42 of 2015 is one of the poverty reduction programs in Cirebon City. The purpose of this study was to determine the company's participation and coordination with the Cirebon City Government in poverty reduction through the CSR program. The research method uses qualitative methods with collection in the form of literature studies, documentation studies, interviews and observations. The result of this research is that the company's participation in coordinating with the Cirebon City Government in poverty reduction through the CSR program is not optimal because the majority of companies carry out CSR programs directly to target groups without coordinating with the Cirebon City Government. The factors that influence the company's participation in coordinating with the Cirebon City Government in poverty reduction through the CSR Program are the sub-optimal leadership of the Mayor of Cirebon, the lack of communication between the Cirebon City Government and company leaders, and the inadequate education of company leaders in the form of awareness, knowledge and understanding of coordination mechanism in the CSR Program.